Nonlinear amplitude versus angle inversion using hybrid quantum ant colony optimization and the exact Zoeppritz equation - Chen, Yuxing; Cheng, Jiwei; Miao, Hongping; Feng, Defu; Wang, Chengci; Zhang, Chao; Song, Mengxin (Frontiers in Earth Science, 2024)
Prestack amplitude versus offset (AVO) inversion is an essential tool to estimate elastic properties. Approximations of P-wave reflection coefficients based on the Zoeppritz equation are limited by the assumption of weak contrast and are inaccurate for far offset, and the existing nonlinear inversion method, like ant colony optimization (ACO), cannot converge to the global optimal solution within a limited time. Consequently, we propose a nonlinear AVO inversion method based on the exact Zoeppritz equation using hybrid quantum ant colony optimization (HQACO). The Zoeppritz equation is a forward modeling approach with high accuracy at far offset and is valid at the strong-contrast interface. HQACO, as a global optimization algorithm, not only has the potential of ACO to search global solutions but also exploits the power of quantum computing to speed up optimization procedures. The self-adaptive rotating strategy is proposed to improve the flexibility and efficiency of the conventional quantum rotating gate largely. Moreover, the quantum gate is introduced to enhance the global search ability. Numerical results show that the average evaluation number required for the global solution decreases largely and the solution converges to the global optimal solution closely using the proposed method. Synthetic applications verify that HQACO shows the most reliable exploring competence to find the global solution. The new inversion method is not only suitable for the strong-contrast interface with noise but also shows promising accuracy using the wide offset range.